Senate Bill No. 1081, Introduced by Senator Alquist - California State Senator Alquist:::::: (1977)
14 page document – Liquefied Natural Gas Terminal Permitting Act of 1977; this bill would repeal restrictions on LGN terminals, grant the Public Utilities Commission (PUC) exclusive power to issues their construction and operations permits, require the PUC to provide a forecast of California's gas supply and demand, and prohibit appropriation or reimbursement to local agencies for costs incurred.